2018
DOI: 10.1590/0104-1428.09516
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polyester polyol modified with polylactic acid as a compatibilizer for plasticized tapioca starch/polylactic acid blends

Abstract: A hyperbranched polyester polyol of the second generation (HBP2) was modified with polylactic acid (HBP2-g-PLA) and employed as a compatibilizer for plasticized tapioca starch (TPS)/polylactic acid (PLA) blends. The effect of the compatibilizer HBP2-g-PLA was evaluated in comparison to the control sample (TPS/PLA blend without HBP2-g-PLA). The torque value of the TPS/PLA blends with HBP2-g-PLA was lower than that of the control sample, while thermal stability and crystallinity followed opposite behavior. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Also, aliphatic hyperbranced polyester provides good hydrophobic and hydrophilic balance, low viscosity, solubility etc. to structure which is modified [22][23][24][25][26][27][28][29][30][31]. For these reasons, aliphatic hyperbranched polyester was chosen as the carrier for p-carborane used as a biomaterial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, aliphatic hyperbranced polyester provides good hydrophobic and hydrophilic balance, low viscosity, solubility etc. to structure which is modified [22][23][24][25][26][27][28][29][30][31]. For these reasons, aliphatic hyperbranched polyester was chosen as the carrier for p-carborane used as a biomaterial.…”
Section: Resultsmentioning
confidence: 99%
“…Murillo and coworkers [27] synthesized hyperbranched alkyd resins from 4 th generation HBP modified with tall oil fatty acids. Murillo and Mesias [28] also modified second generation HBP with polylactic acid to obtain a compatibilizer agent for plasticized tapioca starch/polylactic acid blends. Hyperbranched polyesters having end hydroxyl groups were combined with fatty acids or acrylate used as various resins in coating applications [6,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The same behavior was reported to the TPS/PLA blends, which were compatibilized with MLO, 16 and a hyperbranched polyester polyol modified with PLA. 36 The melting enthalpy (ΔH m ) values of B50GE0 and B50GE5 blends (Table 2) were higher than that of PLA, but that of the B70 followed an opposite behavior. The other blends did not show ΔH m , which also has been observed to TPS/PLA blends activated with epoxidized cardoon oil plasticizer.…”
Section: Dsc Analysismentioning
confidence: 94%
“…Compared with linear polymers, hyperbranched polymers (HBPs) have a highly branched three‐dimensional structure, 28 a large number of active terminal groups, higher solubility and low melt viscosity, 29 thus HBPs were widely used in polymer modification 30–32,21,33,34,29 . Studies 32,33,35 have indicated that the terminal functional groups of HBPs can be used as proton donors or receptors to act on the resin, hydrogen bonding effect was generated between HBPs and the blended resins.…”
Section: Introductionmentioning
confidence: 99%